Shifting mortality patterns of primary liver cancer in the United States: a 20-year analysis of disparities - Zhao, Haiyu; Ma, Lixing (Frontiers in Public Health, 2025)
BackgroundPrimary liver cancer is a leading cause of cancer-related mortality worldwide. Despite its significant disease burden, long-term trends in primary liver cancer mortality across diverse demographic and geographic populations in the United States (U. S.) remain insufficiently characterized.MethodsWe analyzed national mortality data from the Centers for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) database from 1999 to 2020. Deaths were identified using International Classification of Diseases, Tenth Revision (ICD-10) codes C22.0–C22.9, encompassing hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC), and other specified or unspecified liver cancers. Age-adjusted mortality rates (AAMRs) were calculated and stratified by sex, ethnicity, census region, urbanization, and state. Temporal trends were assessed using joinpoint regression to estimate annual percent change (APC) and average annual percent change (AAPC).ResultsBetween 1999 and 2020, AAMRs increased steadily from 9.96 to 14.52 per 100,000 in males and from 4.56 to 6.35 per 100,000 in females, with consistently higher rates in males. Ethnic disparities were evident: non-Hispanic White (NH White) individuals had the lowest AAMRs but showed significant long-term increases (AAPC = 2.02%), whereas non-Hispanic Other (NH Other) populations experienced a decline (AAPC = −1.05%). Hispanic and non-Hispanic Black (NH Black) populations maintained persistently elevated mortality. Geographically, the South and West exhibited the highest AAMRs, although modest declines emerged in some regions after 2015. Both metropolitan and nonmetropolitan areas showed rising mortality, with steeper increases among nonmetropolitan populations. Substantial heterogeneity was observed across states, with most demonstrating positive AAPCs.ConclusionPrimary liver cancer mortality in the U. S. has risen markedly over the past two decades, with pronounced disparities by sex, ethnicity, region, urbanization, and state. These findings highlight the influence of sociodemographic and structural determinants on liver cancer outcomes. Efforts to reduce mortality should focus on equitable access to prevention, early detection, and treatment, particularly for high-burden populations.